2013
DOI: 10.1007/s00404-013-2819-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) improves the sensitivity of CA125 for differentiation of epithelial ovarian cancers from ovarian cysts

Abstract: This study indicates that the addition of VEGF serum value improves the specificity and the sensitivity of CA125 to detect early stage epithelial ovarian cancers, and to differentiate these neoplasms from ovarian cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The introduction of 3D power Doppler systems can The current study augmented the importance of VEGF as a diagnostic marker for malignancy which agree with many other authors [15][16][17][18][19][20][21][22]. The prognostic importance was mentioned in the literature [2,17].…”
Section: Discussionsupporting
confidence: 86%
“…The introduction of 3D power Doppler systems can The current study augmented the importance of VEGF as a diagnostic marker for malignancy which agree with many other authors [15][16][17][18][19][20][21][22]. The prognostic importance was mentioned in the literature [2,17].…”
Section: Discussionsupporting
confidence: 86%
“…These controversial results may be a consequence of the small samples used in studies. Some data indicate that VEGF may be increased in benign gynecological diseases, such as endometrial hyperplasia, abnormal uterus hemorrhage and ovarian cysts (18, 19). In our study, patients with endometriosis had a significantly higher value of mRNA expression for VEGF compared to patients without endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies were shown in Table 1 . 16 25 Of ten studies, six studies were conducted in Western countries, and four studies were conducted in Asian countries. Circulating VEGF was measured with enzyme-linked immunosorbent assay (ELISA) in all included studies.…”
Section: Resultsmentioning
confidence: 99%